Successive differentiation of some mathematical functions using hypergeometric mechanism - Qureshi, MI; Shah, Tafaz ul Rahman; Malik, Shakir Hussain (Annals of Mathematics and Physics, 2023)
In this article, we obtain successive differentiation of some composite mathematical functions: (z)−12sin−1√(z)+√(1−z) ; (z)12sin−1√(z)+√(1−z) ; 4z[1−√(1−z)+ℓn(1+√(1−z)2)] ; 4z2[2√(1−z)−2+z−2zℓn(1+√(1−z)2)] and −4zℓn(1+√(1−z)2) , using a hypergeometric approach as the successive differentiation of these functions can not be performed by any other mathematical technique. 2020 MSC: 33C05, 33B10